2007
DOI: 10.1074/jbc.m700322200
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Regulation of Caspase Activation by Cytochrome Oxidase and Tetramethylphenylenediamine via Cytosolic Cytochrome c Redox State

Abstract: Cytochrome c release from mitochondria induces caspase activation in cytosols; however, it is unclear whether the redox state of cytosolic cytochrome c can regulate caspase activation. By using cytosol isolated from mammalian cells, we find that oxidation of cytochrome c by added cytochrome oxidase stimulates caspase activation, whereas reduction of cytochrome c by added tetramethylphenylenediamine (TMPD) or yeast lactate dehydrogenase/cytochrome c reductase blocks caspase activation. Scrape-loading of cells w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
67
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 87 publications
(71 citation statements)
references
References 19 publications
(32 reference statements)
3
67
1
Order By: Relevance
“…We have previously shown that TMPD and related agents can block caspase activation in cultured cells and cytosolic extracts by reducing the cytochrome c (from c 3+ to c 2+ ), which is then less able to activate the apoptosome (Brown and Borutaite, 2008). TMPD did not significantly inhibit caspases themselves after activation (Borutaite and Brown, 2007), and did not inhibit measured …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously shown that TMPD and related agents can block caspase activation in cultured cells and cytosolic extracts by reducing the cytochrome c (from c 3+ to c 2+ ), which is then less able to activate the apoptosome (Brown and Borutaite, 2008). TMPD did not significantly inhibit caspases themselves after activation (Borutaite and Brown, 2007), and did not inhibit measured …”
Section: Discussionmentioning
confidence: 99%
“…Cytochrome c release activates apoptosis by binding to a cytosolic adaptor protein, APAF-1, which then recruits and activates procaspase-9 within the apoptosome (Li et al, 1997). Recently, we and others have shown that the reduced form of cytochrome c (c 2+ ) has little or no ability to activate the caspases, and that factors that keep the cytosolic cytochrome c reduced during apoptosis induction prevent caspase activation and death of cultured cell lines (Pan et al, 1999;Suto et al, 2005;Borutaite and Brown, 2007). One such factor is N,N,N′,N′-tetramethylphenylene-1,4-diamine (TMPD), which readily crosses cell membranes and rapidly reduces cytochrome c, and can be re-reduced by a number of cellular reductases or reductants (Sarti et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…The redox state of cytochrome c is important in this caspase-dependent apoptosis. Only oxidized cytochrome c can activate the apoptosome, whereas reduced cytochrome c cannot (11)(12)(13). The most potent enzyme that oxidizes cytochrome c is cytochrome c oxidase (13).…”
Section: Discussionmentioning
confidence: 99%
“…Only oxidized cytochrome c can activate the apoptosome, whereas reduced cytochrome c cannot (11)(12)(13). The most potent enzyme that oxidizes cytochrome c is cytochrome c oxidase (13). Multiple caspase-dependent and -independent cell death pathways induce apoptosis after DNA damage (14).…”
Section: Discussionmentioning
confidence: 99%
“…2a). In the activation phase, it has been demonstrated that only ferric cytochrome c is active in the assembly of the apoptosome (50)(51)(52)(53). Based on this observation and the redox reactions of neuroglobin described above, it was hypothesised that neuroglobin might prevent cell death by intervention in the apoptotic pathway by reducing released mitochondrial cytochrome c to the inactive ferrous form (54).…”
Section: Experimental and Computational Studies Of The Role Of Neurogmentioning
confidence: 99%